Florida Master Beekeeper Program Requirements - James D. Ellis; Jerry Hayes; Catherine Zettel Nalen; William H. Kern; Ray Zerba; Brad Burbaugh; Jeanette Klopchin (EDIS)
The Master Beekeeper Program (MBP) is a five-year (minimum) beekeeper training and certification program provided by the University of Florida. One must already be a beekeeper to enter the program. This 22-page fact sheet was written by James Ellis, Jerry Hayes, Catherine Zettel Nalen, William H. Kern, Ray Zerba, Brad Burbaugh, and Jeanette Klopchin, and published by the UF Department of Entomology and Nematology, October 2013.